The capacity of emerging civil engineering contractors - Ramokolo, Bruce; Smallwood, John (University of the Free State, 2008)
Construction management competencies are essential to realise sound practices among and to realise optimum performance by, inter alia, emerging civil engineering contractors. Such competencies enable the success of the business of construction and the management of projects, with increased efficiency and reduced costs as a benefit. The article presents the findings of a Masters study, the objectives in general being to determine the current practices and performance of emerging civil engineering contractors in the Nelson Mandela Bay Metropole. The descriptive method was adopted in the empirical study. The salient findings of the study are: most of the emerging civil engineering contractors do not possess civil engineering related qualifications; construction resources are inappropriately managed leading to construction failures; skills programmes are not well structured and supported; there is a lack of capacity at all management levels of the organisations in terms of managing the business of construction and projects; the nine functions of organisations in the form of general management, technical or production, procurement, marketing, financial, human resources, public relations, legal, and administration and information technology, are not comprehensively represented; and self-ratings indicate inadequacy relative to the controlling function of management work, and relative to certain activities of the organising function. The article concludes that emerging civil engineering contractors lack the requisite competencies and resources to realise sustainable contracting organisations. The article recommends that formal civil engineering and construction management education and training should be promoted throughout the industry for all categories of civil engineering contracting organisations. The article further recommends that all nine functions should be adequately staffed with suitably qualified people in order to manage and undertake the work successfully. Organisations should have the requisite construction-related resources, and owners and managers should market their organisations to ensure the sustainability thereof.

Konstruksiebestuurbevoegdheid is van uiterste belang om deeglike uitvoering van, en optimale werkverrigting deur, onder andere, opkomende siviele ingenieurs, te verseker. Sodanige bevoegdhede verseker die sukses van die konstruksie besigheid en bestuur van projekte, met toenemende doeltreffendheid en ‘n afname in onkoste as bykomende voordeel. Die artikel gee die bevindinge weer van ‘n Meesterstudie, met die oogmerk in die algemeen, om die huidige praktyk en werksprestasie van opkomende siviele ingenieur-kontrakteurs in die Nelson Mandela Metropool, vas te stel. Die beskrywende metode was gebruik in die proefstudie. Die mees uitstaande bevindinge is as volg: meeste van die opkomende siviele ingenieur-kontrakteurs het geen siviele-ingenieur verwante kwalifikasies nie; konstruksiehulpbronne word ondoeltreffend bestuur wat lei tot konstruksie mislukkings; vaardigheidsprogramme word nie goed gestruktureer en ondersteun nie; daar is ‘n tekort aan kapasiteit op alle bestuursvlakke in terme van besigheidsbestuur van konstruksie en projekte; die nege funksies van organisasies in die vorm van algemene bestuur, tegnies of produksie, verskaffing, bemarking, finansies, menslike hulpbronne, publieke skakeling, regsaangeleenthede, en administrasie en inligtingstegnologie, is nie omvattend verteenwoordig nie; en self-evaluering dui onvoldoende beheersfunksie van bestuurswerk aan, en ook met betrekking tot sekere aktiwiteite van die organiseringsfunksie. Die artikel kom tot die gevolgtrekking dat opkomende siviele ingenieur-kontrakteurs tekortskiet aan die nodige bevoegdhede en hulpbronne om volhoubare kontrakteurs-organisasies te verwesentlik. Die artikel beveel aan dat formele siviele ingenieurs- en konstruksiebestuur onderrig en opleiding aangemoedig moet word in die industrie vir alle kategorieë van siviele ingenieur kontrakteur-organisasies. Die artikel beveel verder aan dat al nege funksies voldoende beman word deur toepaslik opgeleide persone, om sodoende die bestuur en onderneming van werk suksesvol te kan uitvoer. Organisasies behoort die vereiste konstruksie verwante hulpbronne te hê, en eienaars en bestuurders behoort hul organisasies te bemark ten einde die lonendheid daarvan te verseker.
Keywords: Emerging contractors; Civil engineering; Construction; Management